Microservice-based scalable online platform for lifelongers - Nguyen, Dinh Hoang (Nanyang Technological University, 2022)
Rapid progression in social developments and technologies has significantly impacted the way people live. As half of the activities carried out by workers could be automated by autonomous systems and robots, it will accelerate the shift in required workforce skills. It means that we should not only focus on human basic literacy but also the need to learn, unlearn and relearn the workforce demanding skills throughout our whole life [1]. As the Internet is becoming more and more popular nowadays and due to the COVID-19 pandemic, people are adopting the online learning approach besides the traditional physical learning method. However, some people do not have the time and commitment to complete a university degree. Whereas some are interested only in parts of the courses rather than completing the degree. Therefore, an online platform, a web application for lifelong learning which is “Learning Tree” would be an essential platform to provide people with such necessary learning opportunities. The modern online learning platform consists of 2 parts, a front-end for end-users including users, admins, and lecturers, and a back-end that processes all the requests such as authentication, authorization, storing user data, etc. Having a good user interface/ user experience design for the front-end part will leverage the user learning journey. In addition, having scalable and effective backend services make the platform be able to serve multiple learners to study concurrently. Therefore, the project’s application server was architected to be service-oriented. Hence, each microservice, such as admin, courses, and community had its own codebase and could be scaled independently, e.g. having more application instances of the specific service.